Dynamic Mechanical and Gel Content Properties of Irradiated ENR/PVC blends with TiO2 Nanofillers - Nur Azrini Ramlee; Chantara Thevy Ratnam; Nur Hashimah Alias; Mohd Faizal Abd Rahman (International Journal of Science and Engineering, 2014)
Numerous studies reported on irradiated epoxidized natural rubber/polyvinyl chloride (ENR/PVC) blends and the blends were found miscible at all compositional range thus it offers a broad of opportunity in modifying the blend characteristic. Addition of low loading titanium dioxide (TiO2) nanofillers in the ENR/PVC blends has shown a remarkable increment in tensile strength. Thus, this study was initiated to address the effect of TiO2 nanofillers on ENR/PVC blends dynamic mechanical and gel content properties and its morphology upon exposure to electron beam irradiation. ENR/PVC blends with addition of 0, 2 and 6 phr TiO2 nanofillers were first blended in a mixing chamber before being irradiated by an electron beam accelerator at different 0-200 kGy irradiation doses. The influence of TiO2 nanofillers on the irradiation crosslinking of ENR/PVC blends was study based on the dynamic mechanical analysis which was carried out in determining the glass transition temperature and the storage modulus behavior of ENR/PVC blends incorporated with TiO2 nanofillers. Formations of irradiation crosslinking in the blend were investigated by gel content measurement. While, the TiO2 nanofillers distribution were examined by Transmission Electron Microscope (TEM). Upon irradiation, the ENR/PVC/6 phr TiO2 formed the highest value of gel fraction. For dynamic mechanical analysis, it was found that electron beam radiation increased the Tg of all the compositions. The relationship between the crosslinking and the stiffness of the nanocomposites also can be found in this study. The enhancement in the storage modulus and Tg at higher amount of TiO2 in the blend could be correlated to the enhancement of the irradiation-induced crosslinking in the nanocomposites characteristic and also with the higher agglomerations of TiO2 evidence shown from  the TEM micrograph examination. Lastly, the dimensions of TiO2 in the blends were found less than 100 nm in diameter which indicates incorporation of TiO2 nanofillers in ENR/PVC blends is potentially to provide the nanocomposites features.  Doi: 10.12777/ijse.6.1.24-30 [How to cite this article:  Ramlee, N.A., Ratnam, C.T., Alias, N.H., Rahman, M.F.A.. 2014. Dynamic Mechanical and Gel Content Properties of Irradiated ENR/PVC blends with TiO2 Nanofillers. International Journal of Science and Engineering, 6(1),24-30. Doi: 10.12777/ijse.6.1.24-30]